Sea surface transport in the Western Mediterranean Sea: A Lagrangian perspective. Issue 12 (2nd December 2013) - Sayol, J.‐M.; Orfila, A.; Simarro, G.; López, C.; Renault, L.; Galán, A.; Conti, D.
Abstract : [2] We study the sea surface transport in the Western Mediterranean Sea from a Lagrangian point of view, in particular the Alboran and the North‐Western subbasins. The study is carried out through the analysis of 3 years of surface velocity model data through Finite Size Lyapunov Exponents, Residence Time, and virtual particle trajectories complementing the classical Eulerian approach. The spatiotemporal variability of the main transport processes is inferred from the Empirical Orthogonal Function modes of the Lyapunov Exponents, being the most relevant modes discussed and physically interpreted. Results indicate that some of the variability in the surface transport patterns in the Western Mediterranean can be explained by specific modes which provide an indication of connectivity among subbasins, like the inflow of Atlantic waters through the Ibiza Channel. Key Points: We use FSLE as a tool to study transport processes of the ocean flow AW deflection in Alboran is related to inflow of water to the Northwestern Residence Time in Alboran is 16 days while in the Northwestern around 45